Cicero Brutus and Orator - Kaster, Robert A. 1948- (Oxford University Press, Incorporated, 2020)
Cicero's Brutus and Orator constitute his final major statements on the history of Roman oratory and the nature of the ideal orator. In the Brutus he traces the development of political and judicial speech over the span of 150 years, from the early second century to 46 BCE, when both of these treatises were written, dispensing praise and criticism, providing an unparalleled resource for the study of Roman rhetoric, and engaging delicately with the fraught political circumstances of the day under the dominance of Julius Caesar. The Orator, written several months later, describes the form of oratory that Cicero most admired, defending his views vigorously against his critics
Keywords: Cicero, Marcus Tullius -- v106-v43 -- Orator; Cicero, Marcus Tullius -- v106-v43 -- Brutus; Cicero, Marcus Tullius.-Brutus; Electronic books